Microbial influences on HPV infection and cervical carcinogenesis: emerging evidence from the vaginal microbiome - Feng, Xue; Song, Wei; Ren, Xinyue; Xu, Zhihui; Li, Chaoyang; Feng, Min; Wang, Nan (Frontiers in Microbiology, 2025)
Microbial communities play a vital role in the human defense system, existing symbiotically with us, contributing to metabolic processes, and strengthening immune defenses against pathogens. A diverse bacterial population in the vagina contributes to maintaining dynamic homeostasis, with their interactions playing a critical role in determining health or disease status. The balanced vaginal microbiota, dominated by Lactobacilli, helps maintain vaginal pH, converts glycogen to lactic acid, and produces bacteriocins and hydrogen peroxide (H2O2), all contributing to its protective functions. On the other hand, an abnormal vaginal microbial composition, characterized by a decrease in beneficial microorganisms, heightens the risk of gynecological diseases such as bacterial vaginosis (BV), sexually transmitted infections, human papillomavirus (HPV) infections, and cervical cancer due to persistent infections. Variation in microbial composition is influenced by factors such as racial background, ethnicity, pregnancy, hormonal fluctuations, sexual behavior, personal hygiene practices, and various physiological conditions. This review aims to offer a detailed overview of the existing literature, focusing on the complex interplay between vaginal microbiota and gynecological conditions such as HPV infection. Our goal is to provide valuable insights that can inform future clinical strategies and interventions.